Survival outcomes after breast cancer surgery among older women with early invasive breast cancer in England: population-based cohort study - Miller, K; Gannon, MR; Medina, J; Clements, K; Dodwell, D; Horgan, K; Park, MH; Cromwell, DA (Oxford University Press, 2024)
Background: This study assessed the influence of age, co-morbidity and frailty on 5-year survival outcomes after breast conservation surgery (BCS) with radiotherapy (RT) versus mastectomy (with or without RT) in women with early invasive breast cancer. Methods: Women aged over 50 years with early invasive breast cancer diagnosed in England (2014–2019) who had breast surgery were identified from Cancer Registry data. Survival estimates were calculated from a flexible parametric survival model. A competing risk approach was used for breast cancer–specific survival (BCSS). Standardized survival probabilities and cumulative incidence functions for breast cancer death were calculated for each treatment by age. Results: Among 101 654 women, 72.2% received BCS + RT and 27.8% received mastectomy. Age, co-morbidity and frailty were associated with overall survival (OS), but only age and co-morbidity were associated with BCSS. Survival probabilities for OS were greater for BCS + RT (90.3%) versus mastectomy (87.0%), and the difference between treatments varied by age (50 years: 1.9% versus 80 years: 6.5%). Cumulative incidence functions for breast cancer death were higher after mastectomy (5.1%) versus BCS + RT (3.9%), but there was little change in the difference by age (50 years: 0.9% versus 80 years: 1.2%). The results highlight the change in baseline mortality risk by age for OS compared to the stable baseline for BCSS. Conclusion: For OS, the difference in survival probabilities for BCS + RT and mastectomy increased slightly with age. The difference in cumulative incidence functions for breast cancer death by surgery type was small regardless of age. Evidence on real-world survival outcomes among older populations with breast cancer is informative for treatment decision-making.